POTONGAN KOMERSIAL KARKAS AYAM BROILER STRAIN COBB YANG MENGALAMI PEMBATASAN PAKAN DAN PEMBERIAN SUMBER SERAT KASAR BERBEDA PADA PERIODE GROWER - Tumiran, Megawati; Rompis, John E. G.; Mandey, Jet S.; Nangoy, Fredy J.; Londok, Jola J.M.R. (Universitas Sam Ratulangi, 2019)
Study was conducted to evaluate the effect of feed restriction and source of different crude fiber on carcass weight and commercial pieces of broiler with Cobb strain. Study was using 24 broilers with Cobb Strain. Restriction of 20 percent feed and different sources of crude fiber were applied to broilers at age of 21to 28 days old. Ration was fed ad libitum to broilers until birds reached age of42 days old. . This research was using a Completely Randomized Design (CRD) in Factorial pattern of 2x4 with 3 replications. As a factor A was restricted feeding consisted of without restrictions (A0), and 20 percents restricted ration (A1). A factor B was source of crude fiber consisted of commercial feed (B0), commercial feed with coffee hull meal (B1), commercial feed with rice bran (B2), and commercial feed with coconut pulp (B3). There were treatment combinations including A0B0, A0B1, A0B2, A0B3, A1B0, A1B1, A1B2 and A1B3. The variables measured were percentages of commercial pieces consist of breast, thigh, wing and brisket. The data analyzed used variance analysis. The honestly significance difference test was used to determine which one of treatment was significantly different from each other. The results showed that the combination treatment of feed restriction and source of crude fiber in feed gave a very significant different effect (P <0.05) on carcass weight of broiler with Cobb strain. Sources of fiber crude affected significantly (P<0.05) percentages of thigh, breast, brisket and live weight. Treatment of feed restriction affected significantly (P<0.05) percentage of wing. Restriction of 20 percents with coconut pulp as source of crude fiber produced better commercial carcass of broilers withCobb strain.Â Keywords: Feed restriction, crude fiber source, broiler commercial pieces, Cobb strain